Effect of the biological protection system on the composition of soil microbiota and quality of potatoes in the central agro‐climatic zone of Krasnodar Territory, Russia - S. N. Nekoval'; O. A. Maskalenko (Юг России: экология, развитие, 2023)
Aim. Assessment of the effect of biological products on soil suppression, biological efficacy, yield and biochemical parameters of potatoes in Krasnodar Territory.Material and Methods. The experiment was carried out on potatoes of the Colomba variety. The biological preparations against potato diseases have been studied. The research was carried out according to generally accepted methods.Results. During the study period, representatives of the genera Alternaria, Fusarium, Verticillium, Cladosporium, Trichoderma, Penicillium, Aspergillus were identified in the complex of soil fungi. When using biological products, an increase in Trichoderma spp. and conditionally suppressive fungi Penicillium spp. and Aspergillus spp. compared with the control and the chemical protection option, by 4.0 and 29.0 times, 1.7 and 1.8 times and 1.4 and 4.5 times, respectively, was observed. The efficacy of the biological products against Alternaria and Fusarium wilt was 73.4–77.7 % in the first year of the research, and 70.0–76.3 % in the second year, which was higher than chemical protection by 3.3–3.8 % and 0.8–2.7 %, respectively. The yield of potato tubers was higher than the control and the chemical protection option by 49.3–10.1 %. The highest content of vitamin C was noted in the biological protection system option. The content of nitrates in all variants of the experiment was within the normal range. The content of starch was higher than the control and the chemical protection option by 1.1–0.2%, respectively.Conclusions. The application of a biological protection system made it possible to reduce the development of Alternaria and Fusarium on potato plants, increase soil suppression, increase yield and improve biochemical indicators.